Isotope Visualization of the North Atlantic Region linked to multinational archaeological research focusing on Norse and Mediaeval periods - Alimu, Nadila (The University of Edinburgh, 2012)
The objective of this research is to investigate the potential use of Google Earth for isotope mapping and visualization. A web-based application system has been developed to allow isotope researchers to view geographic data using Google Earth and query isotope data using Google Chart Tools via a web interface. The system creates methodological framework that visualizes isotope data effectively to aid the analysis of the spatial relationship between isotope values, location and species in multinational areas which include Iceland, Faroe Islands and Greenland. The main study area is Iceland. The functions of the system include spatial querying and statistics. Moreover, users are able to download information about samples that provided isotope values in CSV format files. In the process of developing the system, various programming languages and scripting techniques were applied in this project, including Oracle Spatial, SQL, Perl, KML and HTML.